Implementasi Refleksi Pembelajaran Dalam Proses Pelatihan Di Balai Diklat Keagamaan Surabaya - ., Mushollin (Inovasi: Jurnal Diklat Keagamaan, 2022)
Learning reflection is an important part in the learning and training stages. Reflection on learning will provide more "color" in the meaning of learning (meaningfull learning). The reflection flow has 5 (five) thinking hierarchies, namely (1) Reporting, (2) Responding, (3) Relating, (4) Reasoning, and (5) Reconstructing. ). These stages require a high-level thinking process, namely critical, analytical and creative. The focus of this research is how the training instructors (widyaiswara) carry out the reflection process in 5 stages. The descriptive qualitative is applied in this research. The data was collected through questionnaires techniques, related to reflection patterns. The primary data sources in this study were widyaiswara, while the secondary research data were document data related to BDK Surabaya and also documents related to the learning process in training. The result of this research shows that the widyasiwara have crried out the 5 stages learning reflection well.